Inflation as a Socio-Economic Process: Nature, Types, Causes. The main indicator of inflation is the Consumer Price Index. ("Journal "U". Economy. Management. Finance.", 2020)
The article considers inflation as a socio-economic process that directly affects the economic component of the state, its essence, types, causes, and consequences that affect the whole country as a whole. And also, a statistical indicator is presented (presented) in percentage terms - the Consumer Price Index (CPI), which most clearly reflects the inflationary situation in the country, in this case in the Russian Federation for a certain period of time.
Keywords: inflation; economy; types of inflation; inflation rate; consumer price index